2021
DOI: 10.3390/cancers13153918
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Inflammation in the Development of Breast Cancer

Abstract: Chronic inflammation contributes to the malignant transformation of several malignancies and is an important component of breast cancer. The role of chronic inflammation in the initiation and development of breast cancer from normal breast tissue, however, is unclear and needs to be clarified. A review of the literature was conducted to define the chronic inflammatory processes in normal breast tissue at risk for breast cancer and in breast cancer, including the role of lymphocyte and macrophage infiltrates, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 147 publications
(199 reference statements)
2
55
0
1
Order By: Relevance
“…Ultimately, through the normal inflammatory response, the inflammatory response gradually diminished when the antigen is removed [ 1 , 2 , 3 ]. However, abnormally regulated and sustained inflammatory responses cause secondary illnesses and lead to chronic inflammatory diseases such as asthma and arthritis if not properly treated [ 1 , 2 , 6 , 7 , 8 ]. Although anti-inflammatory agents effectively suppress inflammation, their use is restricted because they cause side effects, such as gastrointestinal disorders [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, through the normal inflammatory response, the inflammatory response gradually diminished when the antigen is removed [ 1 , 2 , 3 ]. However, abnormally regulated and sustained inflammatory responses cause secondary illnesses and lead to chronic inflammatory diseases such as asthma and arthritis if not properly treated [ 1 , 2 , 6 , 7 , 8 ]. Although anti-inflammatory agents effectively suppress inflammation, their use is restricted because they cause side effects, such as gastrointestinal disorders [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the acute phase of the inflammatory response, immune cells migrate to damaged tissues and promote healing by releasing soluble mediators such as cytokines, chemokines, and acute phase proteins [ 1 , 2 , 3 , 4 , 5 ]. Persistent inflammation due to long-term irritation or inappropriate cellular reactions causes tissue damage and fibrosis, leading to chronic inflammatory diseases such as arthritis, asthma, atherosclerosis, diabetes, and cancer [ 1 , 2 , 6 , 7 , 8 ]. Therefore, it is important to properly regulate inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…After that inflammation has been recognized to contribute to malignant transformation of several types of human malignancies, including hepatocellular carcinoma, colorectal cancer and gastric cancer ( Multhoff et al, 2011 ). Inflammation is also a key component of breast carcinogenesis ( Danforth, 2021 ). However, its roles and molecular mechanism in the initiation and progression of breast cancer is still unclear and need to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…At the first stage of malignant evolution, chronic inflammation may play an important role during the initiation, development and prognosis of breast cancer [4], in which chemokines might regulate the migration of immune cells toward the tumor and act as biomarkers for breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…At the first stage of malignant evolution, chronic inflammation may play an important role during the initiation, development and prognosis of breast cancer [4], in which chemokines might regulate the migration of immune cells toward the tumor and act as biomarkers for breast cancer. Studies have shown that CCL-4, -7, -8, -11, -15, -16, -19, -22, -23, -24, -25 and CXCL-5, -8, -9, and -16 were increased in breast cancer compared with normal adjacent breast tissue [5], and genetic polymorphisms near genes encoding CCL-2, -4, -5, -20, -22, CXCL-10, -12 and XCL-1 were found to be associated with the risk and prognosis of breast cancer [6-13].…”
Section: Introductionmentioning
confidence: 99%